Implementation of Servqual Method in Evaluation Applications of Online Learning System in The Faculty of Teacher Training and Education in The University of Dehasen Bengkulu - Belyna Novellya; Liza Yulianti; Hari Aspriyono (Jurnal Komputer, Informasi dan Teknologi, 2021)
During COVID-19, the face-to-face learning process was temporarily replaced by an online learning system. This is done to prevent the spread of COVID-19. But on the other hand, some students complained about the online learning system, especially the material that contained practicum elements, because they could not practice directly and also the material obtained was not easy to understand due to limited feedback and existing networks. In addition, the Faculty of Teacher Training and Education at the University of Dehasen Bengkulu does not yet have an application that can assist students in providing an assessment of the learning system, especially online, so that these complaints are sometimes not conveyed properly. The online learning system evaluation evaluation application at the Faculty of Teacher Training and Education, Dehasen Bengkulu University is an application that was built to make it easier for students to give scores to the online learning system and also make it easier for the faculty to evaluate the assessments given by students. In helping the analysis of student assessment of the online learning system, this application has applied the Servqual Method where the assessment is divided into 2 parts, namely perceptions and expectations. An online learning system evaluation evaluation application at the Faculty of Teacher Training and Education, Dehasen University Bengkulu, was created using the PHP programming language and MySQL database. This application can be accessed online via the link http://belyna.vadapp.my.id/, so students can fill out the assessment anywhere and anytime. Based on the tests that have been carried out, the results show that the functionality of the online learning system evaluation evaluation application at the Faculty of Teacher Training and Education, Dehasen University Bengkulu runs as expected.